Clinical Use of Tailored Computed Tomography to Prevent Poststernotomy Dehiscence - Duman, Zihni M.; Timur, Barış; Topel, Çağdaş; Aksu, Timuçin (The Thoracic and Cardiovascular Surgeon, 2021)
Background Morphological and tissue density analysis of the sternum can be performed in the preoperative computed tomography (CT). The purpose of this study was to analyze morphology and tissue density of sternum in CT and effect for comparison sternal instability.Methods Patients with sternal instability (n = 61) and sternal stability (n = 66) were enrolled in this study. All of the patients were studied using same thorax CT procedure. All the measurements were performed by one specific cardiovascular radiologist. The Hounsfield units (HUs) were measured in axial sections of the sternum trabecular bone.Results Sternal instability group mean HU was 75.36 ± 13.19 and sternal stability group HU was 90.24 ± 12.16 (p < 0.000). HU is the statically significant predictor of sternal instability.Conclusion Our study showed a significant correlation between the mean HU value of sternum and sternal instability. We think that it is important to evaluate the existing thorax CT while performing preoperative risk analysis for sternal dehiscence.
Keywords: sternum; computed tomography; CT scan; wound infection